Evaluation of soil biological properties of 9- and 15-year-old stands in the oil palm plantation in Perak, Malaysia - Karam Singh, Daljit Singh; Abdu, Arifin; Othman, Radziah; Jusop, Shamsuddin; Abdul Hamid, Hazandy; Nik Ab. Majid, Nik Muhamad; I., Zahari; Abd. Halim, Nor Halizah; Cheng, Kah Yen (Academic Journals, 2013)
Opening land for oil palm cultivation provokes many debates around the world regarding on the fate of biodiversity. A study was conducted to evaluate and compare soil biological properties of 9-year-old (P1) and 15-year-old (P2) stands of an oil palm plantation in Bikam, Perak, Malaysia. Composite samples were collected at depths of 0-15 cm (topsoil) and 15-30 cm (subsoil) located within six subplots (20 m × 20 m). The microbial population count was estimated using a spread-plate technique, and the Fluorescein diacetate (FDA) hydrolysis assay was used to measure microbial enzymatic activity. A rapid ethanol-free chloroform fumigation extraction technique was used for microbial biomass extraction, and the extracts were respectively analyzed by wet dichromate oxidation and Kjeldahl digestion for biomass carbon (C) and nitrogen (N). At the 0-15 cm depth, the microbial biomass C and N contents in the soils from both plots were significantly different (P<0.05). At the 15-30 cm depth, only microbial enzymatic activity was significantly different between plots. Although the addition of fertilizers to the soil is believed to be a predisposing factor, no significant differences in P1 and P2 plots for the biomass C and N in soils at the 15-30 cm depth were observed. Variations in the MBC/MBN ratio in soils of the P1 and P2 plots indicate that changes occurring in the soil microbial composition are due to the availability of soil organic substrates and N. Thus establishment of an oil palm plantation does contribute to changes in soil biological properties.